2015
DOI: 10.1007/s00213-015-4103-y
|View full text |Cite
|
Sign up to set email alerts
|

Chronic mild stress alters the somatostatin receptors in the rat brain

Abstract: RationaleThe involvement of somatostatin (SST) and its receptors in the pathophysiology of depression and stress has been evidenced by numerous studies.ObjectivesThe purpose of the present study was to find whether chronic mild stress (CMS), an animal model of depression, affects the SST receptors in the rat brain and pituitary, as well as the level of SST in plasma.MethodsIn CMS model, rats were subjected to 2 weeks of stress and behaviorally characterized using the sucrose consumption test into differently r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 63 publications
(78 reference statements)
1
16
2
Order By: Relevance
“…Such an assumption is also supported by studies, in which the binding of this radioligand was not detected in SST 2 R knockout mice (Hannon et al 2002). In agreement with our previous studies (Faron-Górecka et al 2016), a high density of SST receptors was observed in the control and stressed or/and imipramine treatment groups using [ 125 I]Tyr3-Octreotide binding in different brain areas. Representative autoradiograms are presented in Fig.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Such an assumption is also supported by studies, in which the binding of this radioligand was not detected in SST 2 R knockout mice (Hannon et al 2002). In agreement with our previous studies (Faron-Górecka et al 2016), a high density of SST receptors was observed in the control and stressed or/and imipramine treatment groups using [ 125 I]Tyr3-Octreotide binding in different brain areas. Representative autoradiograms are presented in Fig.…”
Section: Resultssupporting
confidence: 92%
“…Following this experimental paradigm, increased [ 125 I]Tyr 3 -Octreotide binding was observed in all brain regions involved in the stress reaction. These results are contrary to the effect of a shorter period of the CMS protocol (2 weeks), which resulted in a decrease in sst 2 R binding in the studied brain regions (with the exception of the MHb, where an increase in sst 2 R binding was observed, Faron-Górecka et al 2016). However, the opposing effects of 2 and 7 weeks of the CMS protocol are not surprising.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…GAD1 mRNA 59,60 , PVALB mRNA 61 , and SST mRNA 62 signals correspond to previously described distributions. Although cortical SSTR2 mRNA signals were lighter in comparison to some studies 63 , the distribution corresponds to SSTR2 mRNA and SSTR2 binding results in multiple other studies (Supplementary Figure 1A) [64][65][66][67][68] . Control (sense) riboprobe hybridization, for all transcripts, was at background levels (Supplementary Figure 1B, 2).…”
Section: Resultsmentioning
confidence: 58%